2007
DOI: 10.1673/031.007.2001
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Life Stage Specificity of Glutathione S-Transferase Expression in the Hessian Fly,Mayetiola destructor: Implications for Resistance to Host Allelochemicals

Abstract: Two new Delta and Sigma glutathione S-transferases (GSTs) in the Hessian fly, Mayetiola destructor (Diptera: Cecidomyiidae), were characterized and transcription profiles described. The deduced amino acid sequences for the two M. destructor Delta GSTs (MdesGST-1 and MdesGST-3) showed high similarity with other insect Delta GSTs including the conserved catalytic serine residue. The deduced amino acid sequence for the M. destructor Sigma GST (MdesGST-2) showed high similarity with other insect Sigma GSTs includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 52 publications
2
35
0
Order By: Relevance
“…From the blast results, it was evident that there is a general paucity of molecular knowledge in wood boring beetles. Further, multiple sequence alignment with other insect GSTs revealed conserved residues as described previously in other insects (Mittapalli et al, 2007;Wang et al, 2008;Yamamoto et al, 2011;H. Shi et al, 2012) The dominance of the recovered epsilon class GST members perhaps implies the importance of these GSTs during the course of evolution/adaptation of this beetle on its host as observed in other insect groups (Enayati et al, 2005;Ketterman et al, 2011).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…From the blast results, it was evident that there is a general paucity of molecular knowledge in wood boring beetles. Further, multiple sequence alignment with other insect GSTs revealed conserved residues as described previously in other insects (Mittapalli et al, 2007;Wang et al, 2008;Yamamoto et al, 2011;H. Shi et al, 2012) The dominance of the recovered epsilon class GST members perhaps implies the importance of these GSTs during the course of evolution/adaptation of this beetle on its host as observed in other insect groups (Enayati et al, 2005;Ketterman et al, 2011).…”
Section: Discussionsupporting
confidence: 69%
“…A recent study in D. melanogaster suggested that exposure to toxins evoked a coordinated response by the Malpighian tubules, involving the interaction of detoxification pathways (including GSTs) as well as enhanced excretion (Chahine and O'Donnell, 2011). On the other hand, ApGST-E2 was highly expressed in fat body which is also an important metabolic tissue for detoxification as demonstrated earlier in A. planipennis (Mittapalli et al, 2010) and in the Hessian fly, Mayetiola destructor (Mittapalli et al, 2007).…”
Section: Discussionmentioning
confidence: 64%
“…Genetically, the virulent and avirulent Hessian fly larvae in our experiments were identical (biotype L), but their transcriptomes (Mittapalli et al, 2007a(Mittapalli et al, , 2007b(Mittapalli et al, , 2007c and behaviors diverged rapidly due to changes induced in them by different cues from their resistant and susceptible host plants. One important difference was that although the mRNA and protein levels of HFR1 were higher in resistant plants (Subramanyam et al, 2006; Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Error bars represent SD between three biological replicates, with each replicate having 10 larvae. One-way ANOVA was carried out using SAS, and all differences were considered significant at P , 0.05. presumed to function in an attempt to detoxify wheat allelochemicals (Mittapalli et al, 2007b). In addition, avirulent larvae experience oxidative stress, manifested as elevated levels of superoxide dismutase mRNA (Giovanini et al, 2006) along with phospholipid glutathione peroxidase mRNA (Mittapalli et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of GSTs is often tissue-specific (Mittapalli et al 2007). Tissue distributions of GST have been studied in a number of organisms (Chien and Dauterman 1991;Francis et al 2000;Tang et al 2005;Tate et al 1982).…”
Section: Introductionmentioning
confidence: 99%